Linear Segmental Verrucous Epidermal Nevi with Oral Mucosa Involvement: A Rare Case Report - Spandana D. Krishnamurthy; Amrita Hongal; M. Madhu (Indian Journal of Paediatric Dermatology)
Epidermal nevi (EN) are benign cutaneous hamartomas following the lines of Blaschko, originating from postzygotic mutations in embryonic ectoderm. Keratinocytic EN, a subtype, commonly involves the trunk and extremities, with rare oral mucosal involvement. We present a 10-year-old female with linear, hyperpigmented, verrucous plaques on the left face, following Blaschko’s lines, accompanied by ipsilateral tongue discoloration and lip hypertrophy. No systemic abnormalities were noted. Oral verrucous EN (VEN) is rare, with only 16 cases documented globally, typically unilateral and corresponding to cutaneous lesions. Diagnosis relies on histopathology, and management is challenging due to limited guidelines. Treatment is generally unnecessary for asymptomatic cases, but extensive lesions may require surgical or alternative interventions. This case highlights a unique presentation of unilateral keratinocytic EN with ipsilateral oral involvement, emphasizing the need for awareness of its clinical spectrum and consideration of follow-up for potential changes.